Characteristics and outcomes of pharmacy practice experience programs in community pharmacy settings: a scoping review protocol (Research, Society and Development, 2022)
Objective: The objective of this scoping review is to map, identify, characterize, and summarize the evidence on characteristics and outcomes of pharmacy practice experience programs in community pharmacy settings. Introduction: Practice experiences are important components of health professional education programs, including pharmacy. Community pharmacies are accessible to the public, where most pharmacists are concentrated. Despite the relevance of practice experiences in community pharmacies for pharmacy education, the literature still lacks a description of existing programs and their outcomes. Inclusion criteria: This scoping review will consider studies that describe characteristics of pharmacy practice experience programs in community pharmacy settings or evaluate their outcomes. Practice experience programs in outpatient clinics and hospitals will be excluded. Methods: The proposed scoping review will be conducted in accordance with the JBI methodology for scoping reviews. The databases searched will include PubMed, Web of Science and Scopus. The results will be limited to English, Portuguese and Spanish languages and to publications from 1990 to the present. The search for gray literature will include Google Scholar. The extracted data will include characteristics of pharmacy practice experience programs (e.g. teaching activities) or outcomes of the programs evaluated in the studies (e.g. development of knowledge, skills and attitudes by the students). The extracted data will be presented in a tabular format. A narrative summary will accompany the tabulated results and will describe how the results relate to the review’s objective and question, and how the results might inform future pharmacy practice experience programs in community pharmacy settings. The protocol was registered in the Open Science Framework.